Trait association and path analysis for cassava genotypes in four agroecological zones of Nigeria - Aina, O.O.; Dixon, A.; Akinrinde, E. (Science Alert, 2007)
The associations among different traits and their direct and indirect influence on yield using the path analysis and correlation procedures were examined in 20 broad-based cassava genotypes to understand how inter-character relationships influences root yield. Field evaluation was carried out in 4 agroecological zones of Nigeria for two cropping seasons. Data were collected on morphological and yield parameters such as plant height, stem girth, canopy volume, shoot weight, leaf size, number of roots, root size and root yield. Results showed that root parameters such as medium-sized roots with correlation coefficient (r) of 0.95, number of roots (r = 0.91) and small-sized roots (r = 0.77) were highly significantly (p< 0.001) correlated) with root yield. Path analysis revealed that number of roots had the largest direct effect on root yield with a direct path coefficient effect (P) of 0.61, accounting for 86% of the total direct + indirect effects, followed by number of medium-sized roots (p = 0.23), that accounted for 79.2% of the total direct + indirect effects. Small-sized roots had a negative direct effect on root yield (p = -1.21) but a positive indirect effect (p = 1.91) via number of roots. Number of storage roots and medium-sized roots both contributed the largest influence on storage root yield in cassava. These parameters should, therefore, be considered together while selecting for cassava genotypes with higher storage root yield potentials.